PEMANFAATAN LIMBAH PABRIK ROKOK SEBAGAI PUPUK PADA TANAMAN TOMAT (Lycopersicum esculentum Mill) - TYAS SOEMARAH KURNIA DEWI (JURNAL ILMIAH AGRINECA, 2015)
Organic Solid waste of Cigaret not yet used optimaly amount of solid waste that is large enough that 3-4% of the production capacity and the current management is still a lot to do with how stacked in the factory location in a long time. The number of industrial solid waste generated is large enough, then most of the industry in Indonesia has sought to implement solid waste management oriented to exploiting the potential of the waste that can provide added value. Several studies on the characteristics of the solid waste industry in general suggest the potential to be used as compost that can be used to improve soil fertility. This study aims to determine the effect of the time of administration and dose of organic fertilizer from solid waste cigarette factory is best for the plant's growth and yield of tomato. The method used is the factorial withRCD (randomized completely design), consisting of 2 factors, factor 1 is when the solid fertilizer factory waste cigarette (W) consists of a 3 stage treatment: W1 = 14 days before planting, W2 = 7 days before planting, W3 = at planting time. Factor 2 is solid fertilizer factory waste cigarette (D) treatment consists of 3 levels: D1 = 5 tons / ha, D2 = 10 tonnes / ha, D3 = 15 tonnes / ha, and D3 = 20 tonnes / ha, with as many replications 3 times.The results of this study showed1) Current cigarette waste fertilizer (P1 = 14 days before planting, P2 = 7 days before planting, at planting P3 =) no significant effect on plant growth parameters indicated by the parameters of plant height, fresh weight and stover stover dry weight and also no significant effect, on the outcome parameters include parameters during flowering, number of fruits per plant, fruit weight per harvest, leftover fruit per harvest. 2) The dose of cigarette waste fertilizer (D1 = 5 tons / ha, D2 = 10 tonnes / ha, D3 = 15 tonnes / ha, and D4 = 20 tons / ha) did not give a real effect, indicated by the parameters of plant height, fresh weight stover and stover dry weight, and also the outcome parameters include flowering time, and the rest of the fruit per harvest, but the parameters of existing results that show that the real effect of the number of fruits per plant, fruit weight per harvest. 3) The interaction between treatment and time of administration of the dose of fertilizer at the cigarette factory wastes no significant effect on all parameters of growth and yield. 4) The highest of yield Tomato on combination treatment time of administration 14 days before planting with dose of organic fertilizer from solid waste cigarette factory 20 tons / ha (W1D4) is 1490,33 gram/plan.and the lowest (W3D1) is 682.33 g / plant